OP0298 The Role of CD11c+ Dendritic Cells in Inflammatory Arthritis. (10th June 2014) - Puchner, A.; Blüml, S.; Saferding, V.; Goncalves-Alves, E.; Smolen, J.; Redlich, K.
Abstract : Background: Dendritic cells (DCs) play an important role in bridging the innate and the adaptive immune response by serving as antigen presenting cells and are therefore implicated in the initiation of chronic autoimmune diseases, including rheumatoid arthritis. Using two different models of inflammatory arthritis, K/BxN serum transfer arthritis as well as hTNFtg arthritis, both depending only on the innate immune system, we investigated the innate role of dendritic cells in inflammatory arthritis. Methods: We analyzed histological sections of K/BxN serum transfer arthritis as well as hTNFtg arthritis for the presence of CD11c + cells by immunohistochemistry. We also performed synovial biopsies and analyzed the cellular composition of the inflammatory infiltrate with respect to DCs. We used CD11c-diphteria toxin receptor (DTR) transgenic mice, which express the human diphtheria-toxin receptor under the CD11c promoter, allowing for specific depletion of CD11c + cells by administration of diphtheria toxin (DT). K/BxN serum transfer arthritis was induced, and mice were given either DT or PBS. In addition CD11c DTR mice were crossed into hTNFtg animals and also received either DT or PBS. The severity of arthritis was determined clinically and histologically. Results: We show that Cd11 + cells are present in significant numbers in the synovia of K/BxN and TNF driven arthritis. Both myeloid dendritic subsets, CD8 + CD11c + and CD11b + CD11c +, can be found in synovial tissue. In K/BxN serum transfer arthritis, clinical scores showed that CD11c-DTR transgenic mice that received DT had significantly reduced paw swelling and loss of grip strength compared to PBS treated animals. Histological analysis found reduced inflammation after the depletion of CD11c + cells in K/BxN arthritis. In addition local bone destruction and the number of osteoclasts was significantly reduced. Also in TNF-driven arthritis in CD11c-DTR/hTNFtg mice, depletion of CD11c + cells led to a significant reduction of synovial inflammation, as well as local bone erosions. To exclude unspecific effects of DT in mice, wild type animals received DT showed identical clinical and histological signs of arthritis as PBS treated animals. Conclusions: These data show that CD11c + cells are involved in innate reactions leading to inflammatory arthritis and suggest that dendritic cells could be an important therapeutic target for patients suffering from rheumatoid arthritis. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5602